# Tangents and Cotangents of Multiples or Submultiples

We will learn how to solve identities involving tangents and cotangents of multiples or submultiples of the angles involved.

We use the following ways to solve the identities involving tangents and cotangents.

(i) Starting step is A + B + C = π (or, A + B + C = $$\frac{π}{2}$$)

(ii) Transfer one angle on the right side and take tan (or cot) of both sides.

(iii) Then apply the formula of tan (A+ B) [or cot (A+ B)] and simplify.

1. If A + B + C = π, prove that: tan 2A + tan 2B + tan 2C = tan 2A tan 2B tan 2C

Solution:

Since, A + B + C = π

⇒ 2A + 2B + 2C = 2π

⇒ tan (2A + 2B + 2C) = tan 2π

⇒ $$\frac{tan 2A+ tan 2B + tan 2C - tan 2A tan 2B tan 2C}{1 - tan 2A tan 2B - tan 2B tan 2C - tan 2C tan 2A}$$ = 0

⇒ tan 2A + tan 2B + tan 2C  - tan 2A tan 2B tan 2C = 0

⇒ tan 2A + tan 2B + tan 2C = tan 2A tan 2B tan 2C.               Proved.

2. If A + B + C = π, prove that:

$$\frac{cot A + cot B}{tan A + tan B}$$ + $$\frac{cot B + cot C}{tan B + tan C}$$ + $$\frac{cot C + cot A}{tan C + tan A}$$ = 1

Solution:

A + B + C = π

⇒ A + B = π - C

Therefore, tan (A+ B) = tan (π - C)

⇒ $$\frac{tan A+ tan B}{1 - tan A tan B}$$ = - tan C

⇒ tan A + tan B = - tan C + tan A tan B tan C

⇒ tan A + tan B + tan C = tan A tan B tan C.

⇒ $$\frac{tan A + tan B + tan C}{tan A tan B tan C}$$ = $$\frac{ tan A tan B tan C}{tan A tan B tan C}$$, [Dividing both sides by tan A tan B tan C]

⇒ $$\frac{1}{tan B tan C}$$ +  $$\frac{1}{tan C tan A}$$ + $$\frac{1}{tan A tan B}$$ = 1

⇒ cot B cot C + cot C cot A + cot A cot B = 1

⇒ cot B cot C($$\frac{tan B + tan C}{tan B + tan C}$$) + cot C cot A ($$\frac{tan C + tan A}{tan C + tan A}$$) + cot A cot B ($$\frac{tan A + tan B}{tan A + tan B}$$) = 1

⇒ $$\frac{cot B + cot C}{tan B + tan C}$$ + $$\frac{cot C + cot A}{tan C + tan A}$$ + $$\frac{cot A + cot B}{tan A + tan B}$$ = 1

⇒ $$\frac{cot A + cot B}{tan A + tan B}$$ + $$\frac{cot B + cot C}{tan B + tan C}$$ + $$\frac{cot C + cot A}{tan C + tan A}$$ = 1                          Proved.

3. Find the simplest value of

cot (y - z) cot (z - x) + cot (z - x) cot (x - y) + cot (x - y) cot(y - z).

Solution:

Let, A = y - z, B = z - x, C = x - y

Therefore, A + B + C = y - z + z - x + x - y = 0

⇒ A + B + C = 0

⇒ A + B = - C

⇒ cot (A + B) = cot (-C)

⇒ $$\frac{cot A cot B - 1}{cot A + cot B}$$  = - cot C

⇒ cot A cot B - 1 = - cot C cot A - cot B cot C

⇒ cot A cot B + cot B cot C + cot C cot A = 1

⇒ cot (y - z) cot (z - x) + cot (z - x) cot (x - y) + cot (x - y) cot (y - z) = 1.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### 2nd Grade Place Value | Definition | Explanation | Examples |Worksheet

Sep 14, 24 04:31 PM

The value of a digit in a given number depends on its place or position in the number. This value is called its place value.

2. ### Three Digit Numbers | What is Spike Abacus? | Abacus for Kids|3 Digits

Sep 14, 24 03:39 PM

Three digit numbers are from 100 to 999. We know that there are nine one-digit numbers, i.e., 1, 2, 3, 4, 5, 6, 7, 8 and 9. There are 90 two digit numbers i.e., from 10 to 99. One digit numbers are ma

3. ### Worksheet on Three-digit Numbers | Write the Missing Numbers | Pattern

Sep 14, 24 02:12 PM

Practice the questions given in worksheet on three-digit numbers. The questions are based on writing the missing number in the correct order, patterns, 3-digit number in words, number names in figures…

4. ### Comparison of Three-digit Numbers | Arrange 3-digit Numbers |Questions

Sep 13, 24 02:48 AM

What are the rules for the comparison of three-digit numbers? (i) The numbers having less than three digits are always smaller than the numbers having three digits as: